Building inclusive rehabilitation education: A scoping review protocol on EDI approaches and impact - Kristina M. Kokorelias; Vicky Chau; Helana Marie Boutros; Sachindri Wijekoon; Hardeep Singh; Michael Kalu; Maurita T. Harris (PLoS ONE, 2025)
Introduction Equity, diversity, and inclusion (EDI) interventions are critical in fostering accessible and supportive educational environments in rehabilitation professions such as physiotherapy, occupational therapy, and speech-language pathology. These interventions promote cultural competence and reduce systemic inequities, enabling rehabilitation providers to address healthcare disparities and meet the diverse needs of patient populations. Despite increasing awareness, the scope, implementation, and impact of EDI interventions in rehabilitation education remain underexplored. Aim This scoping review aims to map the existing literature on EDI interventions in rehabilitation education, focusing on methods, strategies, and their impact on learners’ outcomes, including cultural competence, professional practice, and attitudes toward diversity. Methods The review follows the Joanna Briggs Institute methodology and PRISMA-Scr guidelines. Studies involving healthcare students and educators in rehabilitation disciplines are eligible. The concept includes EDI-focused interventions, such as curricular reforms, diversity training, and inclusive teaching practices. Eligible contexts include academic and healthcare settings. A comprehensive search strategy will be applied across databases including MEDLINE, EMBASE, and CINAHL, supplemented by grey literature searches. Inclusion criteria follow the Population, Concept, and Context (PCC) framework. Results This review will chart interventions, their educational context, and their outcomes. Key data to be extracted include study design, intervention details, and learner outcomes, emphasizing cultural competence and attitudes. Conclusion Findings will provide a consolidated framework for developing evidence-based EDI interventions in rehabilitation education, addressing gaps in preparing a workforce capable of delivering equitable care in diverse contexts. Recommendations will guide future research and practice, advancing inclusivity and equity in rehabilitation education.